An overview of the effects and mechanisms of m6 A methylation on innate immune cells in sepsis - Qian, Weiwei; Cao, Yu (Frontiers in Immunology, 2022)
Sepsis is a severe clinical syndrome caused by dysregulated systemic inflammatory responses to infection. Methylation modification, as a crucial mechanism of RNA functional modification, can manipulate the immunophenotype and functional activity of immune cells to participate in sepsis progression. This study aims to explore the mechanism of N6-methyladenosine (m6A) methylation modification in immune cell-mediated sepsis through keyword search. Literature retrieval reveals that m6A methylation is implicated in sepsis-induced lung injury and myocardial injury, as well as sepsis-related encephalopathy. Furthermore, it is found that m6A methylation can regulate sepsis by inhibiting the chemotaxis of neutrophils and the formation of neutrophil extracellular traps and suppressing macrophage phagocytosis, thereby playing a role in sepsis.